2014
DOI: 10.1038/onc.2014.143
|View full text |Cite
|
Sign up to set email alerts
|

Activation of mTOR pathway in myeloid-derived suppressor cells stimulates cancer cell proliferation and metastasis in lal−/− mice

Abstract: Inflammation critically contributes to cancer metastasis, in which myeloid-derived suppressor cells (MDSCs) are an important participant. Although MDSCs are known to suppress immune surveillance, their roles in directly stimulating cancer cell proliferation and metastasis currently remain unclear. Lysosomal acid lipase (LAL) deficiency causes systemic expansion and infiltration of MDSCs in multiple organs and subsequent inflammation. In the LAL-deficient (lal−/−) mouse model, melanoma metastasized massively in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 31 publications
4
82
0
Order By: Relevance
“…32 When tested in the lal À/À mouse model, we have recently discovered that LAL deficiencyeinduced inflammation plays crucial roles at all stages of tumor development. 24 In lal À/À mice, B16 melanoma metastasized in the liver and lung of allogeneic lal À/À mice, which was suppressed in allogeneic lal þ/þ mice due to immune rejection. Interestingly and importantly, in addition to the immune suppressive function, we found that MDSCs from lal À/À mice alone directly stimulated B16 melanoma cell in vitro proliferation and in vivo growth and metastasis.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…32 When tested in the lal À/À mouse model, we have recently discovered that LAL deficiencyeinduced inflammation plays crucial roles at all stages of tumor development. 24 In lal À/À mice, B16 melanoma metastasized in the liver and lung of allogeneic lal À/À mice, which was suppressed in allogeneic lal þ/þ mice due to immune rejection. Interestingly and importantly, in addition to the immune suppressive function, we found that MDSCs from lal À/À mice alone directly stimulated B16 melanoma cell in vitro proliferation and in vivo growth and metastasis.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly and importantly, in addition to the immune suppressive function, we found that MDSCs from lal À/À mice alone directly stimulated B16 melanoma cell in vitro proliferation and in vivo growth and metastasis. 24 Cytokines (ie, IL-1b, IL-6, and TNF-a) from lal À/À MDSCs are required for B16 melanoma proliferation. 24 In addition to MDSCs, it seems that hepatocytes were also responsible for production of tumor-promoting cytokines as found here.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations